PREDICTIVE INDEX SUCCESS IN WEANING FROM MECHANICAL VENTILATION IN THE HOSPITAL SAN LUCAS FAG (Fiep Bulletin - online, 2011)
Introduction: A routine frequent in intensive care units is the transition from artificial to spontaneous breathing, this transition is called the weaning from mechanical ventilation, which can result in success or failure. Weaning can be done in a gradual or abrupt with the intent to remove the patient from artificial ventilation and keep the same only in spontaneous ventilation. The physiotherapist has an important role in the conduct of weaning protocols and triage of patients. Objective: Evaluate the success and failure of weaning from mechanical ventilation in ICU patients of São Lucas Hospital FAG. Methodology: Descriptive study performed in a transverse way. After evaluation and approval of the ethics committee of the FAG, data were collected from seven patients admitted to hospital and later St. Luke FAG applied adequate statistical analysis. To conduct the study analyzed the Glasgow Coma Scale, Tobin index, maximal respiratory pressures through manovacuometry: Maximal inspiratory pressure (MIP), and finally, at the time prior PaO2/FiO2 Value of extubation . The study included patients admitted to St. Luke's Hospital and FAG were used in weaning from mechanical ventilation, and we excluded patients who were not in weaning from mechanical ventilation, or less than 24 hours of ventilation or failures that occurred data collection. Results: There were 7 patients being weaned in the ICU of St. Luke's Hospital FAG, which we found a mean Glasgow Coma Scale 11.5 ± 2.43, the average Tobin index was 65 ± 31.2, already Respiratory muscles showed a mean of 28.5 ± 13.17, and finally the ratio obtained by PaO2/FiO2 mean 331.92 ± 115.14. Results: We evaluated 7 patients being weaned in the ICU of St. Luke's Hospital FAG, which we found a mean Glasgow Coma Scale 11.5 ± 2.43, the average Tobin index was 65 ± 31.2, since the pressure Respiratory muscles had a mean of 28.5 ± 13.17, and finally the ratio obtained by PaO2/FiO2 mean 331.92 ± 115.14. Conclusion: With the results we observed that there was success in weaning patients from St. Luke's Hospital FAG according to the parameters, but suggest a further study with a larger sample of patients.
Keywords: Weaning from mechanical ventilation; Mechanical Ventilation; Physiothérapie